Effect of Activin A, Fibrillin-3, and Follistatin on Oocytes Quality and Embryonic Development Following ICSI Cycle - Rasha F Abas (Journal of Global Pharma Technology, 2016)
Objectives: The aim of this study is to elucidate the effect  of  Activin A, Fibrillin-3, and Follistatin hormones on the oocytes  number and quality ,embryonic development, and pregnancy  rate (PR) following intra cytoplasmic sperm injection (ICSI) cycle. Subject, Materials and Methods: Two hundred women undergoing ICSI treatment were chosen randomly. Controlled ovarian stimulation was done with two different protocols. Measurements of Activin A (pg/ml), Fibrillin-3 (ng/ml) and Follistatin (ng/ml) were assessed in serum and follicular fluid on the day of ovum pick up. Intra cytoplasmic sperm injection was performed and the oocyte and embryonic development were evaluated and determined in relation to the levels of these hormones. Results: There was a significant difference between number of MII oocytes and high quality embryos (G1) in pregnant women than that of non-pregnant women. The follistatin follicular fluid (FF) is the only hormone level which has a significant relation with total oocytes and good MII oocytes. Both the mid-cycle level in serum and follicular fluid of activin-A show a negative correlation of around -0.2 with the total number of embryos and the number of G1 embryos. For both Activin A and Fibrillin-3, there was a high or relatively high correlation within the pregnant subject and low till very low correlation in the non-pregnant subjects, independent of the stimulation protocol. Conclusions: The Follistatin FF has a significant correlation with good MII oocytes that could be used as a predictor for successful ICSI outcome.Keywords: Activin A, Follistatin, Fibrillin-3, ICSI, Controlled ovarian stimulation, Metaphase II oocytes, Embryos.